Manx Language Revitalization and Immersion Education - (:unkn) unknown (My University, 2009)
The Manx language is currently enjoying a period of revitalization. The decline of the Manx language as the native vernacular language of the Isle of Man and the subsequent language shift to English are discussed in the first part of this paper. The paper then goes on to consider the revitalization of the language, with the emphasis on Manx-medium immersion education. The results of a questionnaire enquiring into parental motivations for choosing immersion education, and the linguistic backgrounds of the children are then examined in some detail.
Keywords: Language shift; Language revitalization; Immersion education; Parental motivation; Linguistic background